A Case of Asymptomatic Pulmonary Artery Aneurysm with Review of Management Strategies - Muhammad Talha Ayub; Allison Zimmerman; Wajeeha Rasool; Dinesh Kalra; Melissa Tracy; Anupama K. Rao (Case Reports in Cardiology)
Pulmonary artery aneurysm (PAA) is defined as pulmonary artery diameter greater than 4 cm. With advances in cardiac imaging, the detection rate has increased but the natural history remains unknown. We present the case of a large, incidentally identified PAA in a patient with a history of congenital pulmonic stenosis.